Dublin - Boix Tapia, Leonardo; CEDEC (Centro Nacional de Desarrollo Curricular en Sistemas no Propietarios) (2021)
Welcome to this awesome adventure that we are about to begin! In these projects, we are traveling all around the world and we are going to visit some of the most important English-speaking cities and their most outstanding tourist landmarks. We are about to experience the really wonderful and funny experience of learning English in a collaborative way.In this project, we are going to travel to Dublin / Baile Átha Cliath (its name in gaelic) the capital city of the Republic of Ireland, a country which belongs to the European Union. Each session of this project is going to take place in a different and famous part of this magnificent city. In each location, there is a proposal of tasks and activities to deal with the official syllabus.
DBH, 3. eta 4. mailak
Keywords: Curriculumeko baliabideak; Baliabide digitalak; Eduki digital didaktikoak; Erronketan oinarritutako ikaskuntza